Second-order intermodulation mechanisms in CMOS downconverters. - Manstretta, D.
An in-depth analysis of the mechanisms responsible for second-order intermodulation distortion in CMOS active downconverters is proposed in this paper. The achievable second-order input intercept point (IIP2) has a fundamental limit due to nonlinearity and mismatches in the switching stage and improves with technology scaling. Second-order intermodulation products generated by the input transconductor or due to self-mixing usually contribute to determine the IIP2 even though they can, at least in principle, be eliminated. The parasitic capacitance loading the switching-stage common source plays a key role in the intermodulation mechanisms. Moreover, the paper shows that, besides direct conversion and low intermediate frequency (IF), even superheterodyne receivers can suffer from second-order intermodulation if the IF is not carefully chosen. The test vehicle to validate the proposed analysis is a highly linear 0.18-μm direct-conversion CMOS mixer, embedded in a fully integrated receiver, realized for Universal Mobile Telecommunications System applications.
Keywords: 0.18 micron; CMOS active downconverter; UMTS; Direct conversion architecture; Fully-integrated wireless receiver; Linear direct-conversion CMOS mixer; Low intermediate frequency architecture; Parasitic capacitance; Second-order input intercept point; Second-order intermodulation distortion; Self-mixing.; Superheterodyne receiver; Switching-pair mismatch; Switching-stage common source; Transconductor nonlinearity